Persepsi ibu tentang imunisasi DPT hubungannya dengan partisipasi ibu dalam membawa anaknya untuk imunisasi DPT=Mother's Perception About DPT Immunization the Correlation with Mother's Participation on DPT Immunization P - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1988)
ABSTRACT The purpose of this study was to examine DPT mother's immunization behavior in the Godean subdistrict The population of the Godean subdistrict was chosen ?WV," se it was one of the first Expanded Programme on Immunization efforts in the Yogyakarta province and still has a high drop out rate. A Cross Sectional approach was utilized to study 372 house wiles who have children aged 7 to 24 months. Regression analysis was used to analyses the data Percieved threat of the diseases, perceived benefits of preventive action, perceived barriers to preventive action, and advice from others about DPI. immunization, significantly influenced mother's DPT immunization behavior. Perceived barriers on the mother's part, especially ignorance about the benefits of immunization and DPT immunization procedures, had the strongest predictive power. Advice from others showed the second strongest predictive power,with health cadres giving the biggest contribution next to doctors and vaccinators. Perceived susceptibility to the diseases gave a bigger contribution than perceived severity of diseases.